PLANT REGENERATION FROM MESOPHYLL PROTOPLASTS OF POTATO (SOLANUM TUBEROSUM L.) CULTIVAR DELAWARE USING SILVER THIOSULFATE (STS) (Journal of Sciences, Islamic Republic of Iran)
The use of in vitro potato shoot cultures for protoplast isolation is desirable for consistent protoplast qualities. Ethylene build-up in the culture vessels causes problems for leaf growth (e.g. decreasing leaf surface, dry weight and chlorophyll) in shoot culture. Fifty to one hundred µM Silver thiosulfate (STS) produced a larger leaf area as a source of plant material for protoplast isolation. STS also decreased the internode length of potato shoots but increased dry weight and chlorophyll. Regenerated plants were obtained from cultured protoplasts in a series of media based on the MS medium. Protoplasts of Delaware showed a better response in cell division and colony formation in agarose-solidified culture medium. Regenerated plants showed some degrees of aneuploid but basically were similar to the original potato plants.